2004
DOI: 10.1038/sj.cgt.7700673
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral-mediated PTEN transgene expression sensitizes Bcl-2-expressing prostate cancer cells to radiation

Abstract: Bcl-2 is associated with resistance to radiotherapy in prostate cancer. It was recently demonstrated that transduction of LNCaP prostate cells with the PTEN gene resulted in Bcl-2 downregulation. We hypothesized that forced expression of PTEN in prostate cancer cells would sensitize cells to radiation, downregulate Bcl-2 expression, and potentiate the G2M block induced by radiation. Four cell lines -PC-3-Bcl-2 (Bcl-2 overexpression, deleted PTEN), PC-3-Neo (wild-type Bcl-2, deleted PTEN), LNCaP (Bcl-2 overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 16 publications
1
40
0
Order By: Relevance
“…48,49 This recovery of radiation sensitivity was attributed to the ability of PTEN to suppress DNA repair capacity. 50 In contrast, Shen and coworkers reported that PTEN is important for DNA DSB repair by regulating Rad51 expression 4 and that PTEN influences γ-H2AX as well as 53BP1 of spindle assembly checkpoint, a well characterized pathway to genomic instability.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 This recovery of radiation sensitivity was attributed to the ability of PTEN to suppress DNA repair capacity. 50 In contrast, Shen and coworkers reported that PTEN is important for DNA DSB repair by regulating Rad51 expression 4 and that PTEN influences γ-H2AX as well as 53BP1 of spindle assembly checkpoint, a well characterized pathway to genomic instability.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of functional PTEN and the subsequent activation of the PI3K/Akt pathway may render cells more resistant to radiation treatment in advanced prostate cancer. Rosser et al (50) showed that adenoviral-mediated PTEN transgene expression sensitizes prostate cancer cells to radiation. Our study confirms the results from the earlier study and extend to show that the presence of PTEN enhances the radiosensitization effect of parthenolide, in part, by suppressing the absolute amount of activated p-Akt.…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports have indicated that restoring PTEN function in PTEN-defective cells using gene transfer approaches radiosensitizes human glioma 19 and prostate carcinoma 20 cells. The molecular mechanism responsible for the radiosensitizing properties of Ad-PTEN has not been known, and the ability of Ad-PTEN to retard the repair of radiation-induced DSBs, shown here, has not been demonstrated before.…”
Section: Adenoviral Pten Enhances Radiosensitivity G Pappas Et Almentioning
confidence: 99%
“…20 Mutations in PTEN are relatively frequent in prostate cancer, but its status in NSCLC has been studied less often. One study found that abnormalities of the PTEN gene were involved in only a small subset of lung cancers.…”
Section: Introductionmentioning
confidence: 99%